1999
DOI: 10.1006/bulm.1999.0131
|View full text |Cite
|
Sign up to set email alerts
|

Reaction and Diffusion on Growing Domains: Scenarios for Robust Pattern Formation

Abstract: We investigate the sequence of patterns generated by a reaction-diffusion system on a growing domain. We derive a general evolution equation to incorporate domain growth in reaction-diffusion models and consider the case of slow and isotropic domain growth in one spatial dimension. We use a self-similarity argument to predict a frequency-doubling sequence of patterns for exponential domain growth and we find numerically that frequency-doubling is realized for a finite range of exponential growth rate. We consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
400
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 333 publications
(418 citation statements)
references
References 27 publications
16
400
2
Order By: Relevance
“…3). This is similar to the asymmetries observed for high strain rates for uniform domain growth reported in Crampin et al (1999). This represents a smooth modulation of the frequency-doubling sequence.…”
Section: Nonuniform Domain Growthsupporting
confidence: 87%
See 4 more Smart Citations
“…3). This is similar to the asymmetries observed for high strain rates for uniform domain growth reported in Crampin et al (1999). This represents a smooth modulation of the frequency-doubling sequence.…”
Section: Nonuniform Domain Growthsupporting
confidence: 87%
“…We have shown that for small spatial perturbation, which we interpret as gentle gradients in the spatial dependence, we recover mode-doubling-type sequences (at least for the low modes that we have monitored). For more strongly nonuniform growth (for steeper change in S) at high ρ we have observed asymmetry, as for the uniform case, and for lower ρ selected peaks fail to undergo transitions, akin to the failure of mode-doubling for uniform linear growth (Crampin et al, 1999). For highly nonuniform domain growth, in particular when one region of the domain is not growing, other sequences may be formed by the failure of peak splitting (or insertion) at particular locations, specifically for those peaks on the stationary part.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations